Student readiness on a newly-designed blended learning English language proficiency course in UiTM / Nur Fatima Wahida Mohd Nasir, Izaham Shah Ismail - Mohd Nasir, Nur Fatima Wahida; Ismail, Izaham Shah (Penerbit UiTM (UiTM Press), 2015)
In the field of education, technology has developed vastly in becoming one of the main media of instruction in schools, institutions or even training programmes. Educators from all over the world are now looking into new implementations in replacing the old conventional way of teaching to enhance a better learning environment among students in this era of globalization. Special attention is now focusing into what is known as a combination of e-learning and face to face learning (F2F) called blended learning. This paper was conducted among 156 Diploma undergraduates of the Universiti of Teknologi MARA (UiTM) Shah Alam, Malaysia which investigated students’ readiness of a newly-designed blended learning English language proficiency course under the Academy of Language Studies (ALS). Correlation between students’ readiness and their enjoyment going through the new course is also investigated. Findings indicate that Diploma students of UiTM Shah Alam exhibit above-medium levels of readiness toward blended learning and that there is a negative correlation between students’ readiness with their enjoyment going to ELC classes. Further recommendations of the research are also discussed in the paper.